The Effect of Resilience on Psychological Well-Being in Parents with Children with Special Needs in Berau Regency - Hilda Maulidatul Rahma; Dewi Kamaratih (Journal of Social Research, 2026)
Parents who raise children with special needs often experience various psychological challenges that may affect their psychological well-being. The increasing number of children with special needs in Indonesia highlights the importance of understanding factors that support parents’ mental health. One factor believed to play an important role is resilience, which refers to the ability of individuals to adapt and remain strong when facing difficult situations. This study aims to examine the effect of resilience on psychological well-being among parents of children with special needs in Berau Regency. The study employed a quantitative inferential approach with a sample of 186 parents selected using a snowball sampling technique. Data were collected using a resilience scale developed by the researchers and the Psychological Well-Being Scale based on Ryff’s model. The data were analyzed using simple linear regression after meeting the assumptions of normality and linearity. The results showed that resilience had a significant positive effect on psychological well-being (B = 0.485; p < 0.05). The coefficient of determination indicated that resilience contributed 60.8% to the variance in psychological well-being. These findings suggest that higher levels of resilience are associated with higher psychological well-being among parents of children with special needs. Therefore, strengthening resilience is important for supporting parents’ psychological health and improving their ability to cope with parenting challenges.